Systematic review: management of localised low‐grade upper gastrointestinal neuroendocrine tumours. Issue 12 (11th May 2020) - Exarchou, Klaire; Howes, Nathan; Pritchard, David Mark
Summary: Background: Neuroendocrine tumours (NETs) of the stomach and duodenum are rare, but are increasing in incidence. Optimal management of localised, low‐grade gastric and duodenal NETs remains controversial. Aims: To systematically review recent literature that has evaluated the management of localised low‐grade gastric and duodenal NETs. Methods: A systematic literature search was conducted. Articles were screened and eligible articles fully assessed. Additional articles were identified through the included articles' reference lists. Results: Several relevant retrospective case series were identified, but there was considerable heterogeneity between studies and they reported a variety of parameters. Type I gastric NETs had an excellent prognosis and conservative management approaches such as endoscopic surveillance/resection were appropriate in most cases. Many type III gastric NETs were low grade and appeared to have a better prognosis than has previously been appreciated. Endoscopic rather than surgical resection was therefore effective in some patients who had small, low‐grade tumours. Duodenal NETs were more heterogenous. Endoscopic resection was generally safe and effective in patients who had small, low‐grade, nonfunctional, non‐ampullary tumours. However, some patients, especially those with larger or ampullary duodenal NETs, required surgical resection. Conclusions: Most type I gastric NETs behave indolently and surgical resection is only rarely indicated. Some type III gastric and duodenal NETs have a worse prognosis, but selected patients who have small, localised, nonfunctional, low‐grade tumours are adequately and safely treated by endoscopic resection. Due to the complexity of this area, a multidisciplinary approach to management is strongly recommended.